2019
DOI: 10.1017/jfm.2019.112
|View full text |Cite
|
Sign up to set email alerts
|

Linear iterative method for closed-loop control of quasiperiodic flows

Abstract: This work proposes a feedback-loop strategy to suppress intrinsic oscillations of resonating flows in the fully nonlinear regime. The frequency response of the flow is obtained from the resolvent operator about the mean flow, extending the framework initially introduced by McKeon & Sharma (J. Fluid Mech., vol. 658, 2010, pp. 336–382) to study receptivity mechanisms in turbulent flows. Using this linear time-invariant model of the nonlinear flow, modern control methods such as structured ${\mathcal{H}}_{\in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 102 publications
1
46
0
Order By: Relevance
“…It should be mentioned that the largest drag increase among all DNS runs was observed for ∠Â d = 3π/4 and y + d = [20,25]. The Re τ of these runs increased by more than a factor of 2 and the simulations developed numerical instabilities due to insufficient grid resolution before a statistically steady state was reached.…”
Section: A Comparison Between the Rank-1 Resolvent Model And Dnsmentioning
confidence: 91%
See 2 more Smart Citations
“…It should be mentioned that the largest drag increase among all DNS runs was observed for ∠Â d = 3π/4 and y + d = [20,25]. The Re τ of these runs increased by more than a factor of 2 and the simulations developed numerical instabilities due to insufficient grid resolution before a statistically steady state was reached.…”
Section: A Comparison Between the Rank-1 Resolvent Model And Dnsmentioning
confidence: 91%
“…Yeh and Taira [24] used the gains of the uncontrolled resolvent operator as proxy to identify adequate control parameters for separation control over an airfoil and showed that parameter combinations with high uncontrolled gain correspond to favorable controller settings. Leclerq et al [25] considered and controlled a two-dimensional incompressible open-cavity flow using structured H ∞ synthesis on a sequence of linear flow models, where each flow model of the sequence is based on the resolvent operator about the mean of the previous controlled flow. Their study shows that the controller is able to successfully suppress the oscillations in a sequence of five controllers.…”
Section: B Opposition Control and Low-order Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The response of coaxial two-fluid atomizers to a wide range of swirling and non-swirling gas co-flows has been investigated extensively (Aliseda et al, 2008;Eggers and Villermaux, 2008;Lasheras et al, 1998;Marmottant and Villermaux, 2004), providing the theoretical and experimental basis for this feedback control work. Additionally, over the last decade data reduction methods have been extensively applied for the reduced order description and control of fluid flows (Blanchard and Sapsis, 2019;Grenga et al, 2018;Hervé et al, 2012;Huang et al, 2017;Krolick and Owkes, 2018;Leclercq et al, 2019;Mohan and Gaitonde, 2017;Rabault et al, 2019;Rowley and Dawson, 2017;Schmid et al, 2011;Tallet et al, 2016). Here, we present a method to perform feedback closed-loop control of a spray atomizer where the control input consists of measurements of light attenuation across the depth of the spray at 10 gas diameters downstream of the nozzle and where the control actuation is on the swirl and no-swirl gas flow rates (defined over ranges that span the desired momentum ratios and swirl ratios of interest).…”
Section: Introductionmentioning
confidence: 99%
“…Ψ in (3.2)) (Bagheri et al 2009)? (ii) Can the GLE work on non-modal (Chen & Rowley 2011), quasi-periodic (Leclercq et al 2019) or multi-mode systems (Carini, Auteri & Giannetti 2015)? (iii) Can nonlinear effects be ignored (Leclercq et al 2019)?…”
Section: Discussionmentioning
confidence: 99%